Responsabilidade tributária dos sócios-gestores na dissolução irregular da empresa - Cruz, Juliana Campos de Carvalho (2022)
The general objective of this research is to develop an analysis of the understanding of the rule established in article 135, item III, of the National Tax Code, concerning the tax liability of managing partners, based on the theoretical framework studied, in order to demonstrate that the Precedent nº 435 issued by the Superior Court of Justice expanded the possibilities of liability of the managing partners of the limited liability company, in disagreement with the Constitutional Text of 1988 and with the complementary legislation that gave rise to it. The hypothesis, in the end proven true, highlights the competence of the complementary rule, more specifically, of the National Tax Code, for the purpose of delimiting the tax liability of third parties, demonstrating that the rule contained in the summary statement expanded the hypotheses of liability without support in the order constitutional. The research starts from a review of the literature on the subject, with a hypothetical-deductive methodological approach in which, according to the hypothesis elaborated, it seeks proof in the intellectual production of the actors who work with the theme, both theoretical (through scientific articles, books, etc) and concretely, through analysis of judicial decisions and legislation. In the end, it was concluded that the interpretation given by the Superior Court of Justice to the tax liability rule offended the Federal Constitution, not only subverting the staggered structure of the legal system, but also, transcending its judicial function by interfering in the legislative field.